The relationship between leadership styles, communication competence and employees' job satisfaction in private Universities of the UAE - Hijazi, Shadi Mousa Mohammad (2017)
Previous studies have documented the importance of the leadership style and communication competence of the leaders and their relationship with employees` job satisfaction. However, there was a lack of leader insight regarding this relationship in the context of higher education in the United Arab Emirates and very few literature had discussed the issues. Transformational style has greater relationship with job satisfaction than transactional style but the results of previous studies were still contradictory. The purpose of this study was to examine the relationships between leadership styles, communication competence and the job satisfaction of the employees in the UAE private universities. Besides, the study had also identified the influence of communication competence and leadership styles toward job satisfaction. The quantitative method was used in data collection. A random sampling technique was conducted which comprised of 247 faculty members and staff from seven private universities in UAE. A total of three different sets of instruments were used, namely Multifactor leadership (MLQ), Communicative Competence Scale (CCS) and the Minnesota Satisfaction Questionnaire (MSQ). Descriptive statistics was used to describe the sample characteristics and Pearson correlation was used to examine relationship between the independent variables and dependent variable. Multiple Regression test was used to testify the influence of predictor factors on job satisfaction. The results of the study indicated that there was a positive and significant relationship between transformational style and communication competence. However, the relationship between transactional leadership style and job satisfaction was observed to be negative but significant. Findings had revealed that transformational and transactional leadership styles and communication competence were predictors of job satisfaction specifically on the intrinsic and extrinsic factors. The current study had provided support for the previous theories about leadership, communication and job satisfaction. Practically based on the current study findings, transformational leadership style is more appropriate in higher education context rather than transactional style as it led to higher job satisfaction. An effective leader‘s communication competence had increased the employee‘s job satisfaction.